Synthetic Aperture Radar Interferometry (InSAR): Application to ground deformation studies for volcano and seismic monitoring - Romero, R.; Carrasco, D.; Luzón, F.; Martínez, A.; Rodríguez-velasco, G.; Moreno, V.; Araña, V.; Aparicio, A.; Fernández, J. (Física de la Tierra, 2002)
Several applications of InSAR in volcano and seismic areas are described. The aim is to demonstrate the utility of this space technique for routine monitoring in these hazard areas and show that satellite radar interferometry could be routinely integrated in operational volcano monitoring procedures as a complement to other collected data or as a monitoring technique on its own. The scenarios chosen were the Canary Islands (Tenerife, Lanzarote y La Palma) and in a second stage, Ecuador (Tungurahua volcano and Galapagos islands). Results obtained have been very different in every scenario: at Tenerife island we have found two deformations outside the usual monitoring areas and have verified the results of no deformations previously obtained in Las Cañadas Caldera with ground surveys; at Lanzarote and La Palma islands we have not found any deformations greater than 3 cm. Ground deformations have been obtained in Galapagos Islands, due to recent eruptions and no deformation has been found in Tungurahua volcano, despite very recent eruptions. Moreover, seismic studies in South of Iberian Peninsula (Adra earthquake in 1993) have shown displacements, still under consideration.